The Perception of Intermediate Students Regarding Awareness, Image, and Career Choice of Nursing Profession in Dera Ghazi Khan - Mukhtar , Madiha; Arshad, Sidra; Rana, Atooba; M Saifullah (Future Science, 2020)
Health care system is envolving and the services demand are increasing. As the important workforce in health care system, nurses play a critical role in health promotion, disease prevention and delivering primary and community care. This study was aimed to observe the perception of higher secondary school students regarding nursing Profession in Dera Ghazi khan. A cross-sectional study method was applied to 112 students of intermediates of 3 different private sectors. Data collected from 60 males and 52 females. Data were collected by a valid and reliable tested questionnaire and analyzed by descriptive statistics (mean + standard deviation). Questionnaire was about the evaluation the perception of respondents regarding awareness, image and career choice of nursing profession. The results obtained that 88% respondents were aware about the nursing profession and duties. As 79.4% respondents accepted that “Nursing is a respected profession”. As 38% respondents did not consider nursing as career choice. regarding the nursing profession This study was revealed that the percentage of males about awareness, image and career choice are higher than females. The difference in percentage can be due to higher frequency of males (60) as compared to females (52). The average of male regarding awareness is 30 % and in females is 25 %. The average of males about nursing image is 30 % and of females is 39 % Average percentage of males about nursing image is 48% and of females is 39%.